Validity and reliability of a new hip flexor muscles flexibility assessment tool: The reactive hip flexor (RHF) test - González-de-la-Flor, Á.; García-Pérez-de-Sevilla, G.; Domínguez-Balmaseda, D.; del-Blanco-Muñiz, J. Á. (Physical Therapy in Sport, 2023)
Background The modified Thomas test is the most used and most reliable test to assess the hip flexors` flexibility. However it does not evaluate the interaction of both legs. The objective of this study is to propose a new assessment tool for hip flexor flexibility, the Reactive Hip Flexion (RHF) Test.